Fat‐based registration of breast dynamic contrast enhanced water images. Issue 4 (26th July 2017) - Srinivasan, Subashini; Hargreaves, Brian A.; Daniel, Bruce L.
Abstract : Purpose: In this study, a 3D fat‐based deformable registration algorithm was developed for registering dynamic contrast‐enhanced breast images. Methods: The mutual information similarity measure with free‐form deformation motion correction in rapidly enhancing lesions can introduce motion. However, in Dixon‐based fat‐water separated acquisitions, the nonenhancing fat signal can directly be used to estimate deformable motion, which can be later used to deform the water images. Qualitative comparison of the fat‐based registration method to a water‐based registration method, and to the unregistered images, was performed by two experienced readers. Quantitative analysis of the registration was evaluated by estimating the mean‐squared signal difference on the fat images. Results: Using a scale of 0 (no motion) to 2 ( > 4 voxels of motion), the average image quality score of the fat‐based registered images was 0.5 ± 0.6, water‐based registration was 0.8 ± 0.8, and the unregistered dataset was 1.6 ± 0.6. The mean‐squared‐signal‐difference metric on the fat images was significantly lower for fat‐based registered images compared with both water‐based registered and unregistered images. Conclusions: Fat‐based registration of breast dynamic contrast‐enhanced images is a promising technique for performing deformable motion correction of breast without introducing new motion. Magn Reson Med 79:2408–2414, 2018. © 2017 International Society for Magnetic Resonance in Medicine.